Human Rights Protection and Criminal Liability in the Smuggling of Indonesian Migrant Workers - Anita Zulfiani; Muna Ganesya Arya; Nabila Alinka Wibowo; Tika Andarasni Parwitasari; Yussri Sawani (Universitas Lampung, 2025)
This research examines the criminal liability of Indonesian migrant workers involved in migrant smuggling, whether intentionally or unintentionally, within the framework of human rights and criminal law. Using a doctrinal legal approach, the study finds that migrant workers, as victims of human trafficking, cannot be held criminally liable for smuggling since they are treated as objects of the crime, although they may still be accountable for other offenses under applicable law. Criminal liability rests with individuals or organized groups that profit from smuggling activities. The study emphasizes the need to protect the rights of Indonesian migrant workers and to prevent the criminalization of those who become victims of human trafficking.